(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
The way in which humans defend themselves can be either a deliberate action or an automatic coping reaction. Both forms are briefly described before the focus shifts to the structure of coping reactions in general. A preliminary distinction between power and violence provides a basis for understanding the role of aggression. The main part of the paper describes typical forms of aggression and their corresponding existential themes, which relate to the four fundamental existential motivations.